Formation of the land market in Ukraine: methodological aspect (Economics and region, 2022)
The problem is to develop a mechanism for efficient use of land resources in Ukraine on the basis of private land ownership. Solving the problem at the methodological level of institutionalism involves deepening the existing system of philosophical and economic attitudes to land resources in society. It is necessary to improve the existing methodological approaches, to develop progressive mechanisms for regulating the management system of land use and reproduction. The problem of improving methodological approaches to the separation and distribution of land rent, effective management of lease rights, minimization of natural and economic risks, elaboration of the principles of transition to sustainable land use is acute. On this basis, it is legitimate to recommend flexible concepts for the development of land relations.
Keywords: land market; land relations; private land ownership; land price; monetary valuation; methodology of institutionalism